Efektivitas Penggunaan Media Visual terhadap Keterampilan Menulis Puisi Siswa Sekolah Dasar - Wahyuningsih, Fitri Marliyah; Giwangsa, Sendi Fauzi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
Writing poetry is often considered challenging for elementary school students due to a lack of imagination, mastery of diction, and limited use of relevant teaching media. This study aims to examine the effectiveness of using visual media in improving the poetry writing skills of elementary school students. The study employed a quantitative approach with a pre-experimental